Kaji Dampak Pembangunan Infrastruktur Transportasi Terhadap Pertumbuhan Inklusif Ekonomi Regional - Al Fadhil, Mursyid; Haris, Abdul; Muhimmah, Baiq Ratna (Jurnal Magister Ekonomi Syariah, 2023)
The development of good transportation infrastructure (freeways) will greatly help the development of a region, business or business activities in an area will be increasingly stretched along with the better availability of road infrastructure which is access to the area. one of which is the construction of a freeway in Lampung province as the gateway to the island of Sumatra. This research wants to know how the impact of transportation infrastructure development has on regional economic inclusive growth. The research method used is quantitative with the Paired Sample t-Test and Wilcoxon and multiple regression using the Random Effect Model. The results of this study reveal that of the five variables, only the GRDP variable has no significant changes. Then the results of the regression test before the presence of the freeway showed that there was a significant influence on the human development index on GRDP, while the results after the freeway had an influence, namely the variable human development index, and labor force participation.